Modulation of sphingolipids, cholesterol and saturated fatty acids interact with the neurodegeneration in the Drosophila blue cheese mutant. - Boo, George. (2011)
The accumulation of insoluble ubiquitinated protein aggregates characterizes many neurodegenerative diseases such as Alzheimer’s disease. Some of these diseases are associated with perturbation of sphingolipids and cholesterol homeostasis. To elucidate the association between aberrant metabolism of lipids and age-related neurodegeneration, we study the Drosophila neurodegenerative blue cheese (bchs) mutant. bchs is associated with lysosomal trafficking and autophagosomal degradation of aggregated proteins. In this study, pharmacological interventions as well as augmented cholesterol and fatty acid diets were used to assay possible interactions between lipid metabolism and the autophagic pathway which might bring about the bchs neurodegenerative phenotype. Cholesterol levels in wandering bchs third instars larvae, whose phenotypes that have either been exacerbated or ameliorated by different treatments, were enzymatically analyzed and quantified. Drugs associated with induction of autophagy such as Rapamycin, Metformin and Resveratrol rescued bchs neurodegenerative phenotype. Whereas drugs associated with suppression of autophagy such as Myriocin and Fumonisin B1 exacerbated bchs neurodegeneration. Cholesterol feeding led to excessive sterol accumulation in larvae and exacerbated the bchs neurodegenerative phenotype. Moreover, sphingolipids may be involved in this process; sphingolipid metabolic inhibitors such as Myriocin and Fumonisin B1 which lower ceramide levels in bchs mutants resulted in further exacerbation of the degenerative phenotype.